Impacts of a Recent Interdecadal Shift in the Summer Arctic Dipole on the Variability in Atmospheric Circulation over Eurasia - Zhang, Xuanwen; Pang, Xueqi; Zhang, Xiang; Wu, Bingyi (Atmosphere, 2024)
This study investigated the relationship between the summer Arctic Dipole (AD) anomaly and the climatic variability in Eurasia during the period 1979–2021. It was found that the summer AD anomaly experienced a phase shift from frequent negative phases before 2006 to positive phases after 2007, as manifested by the shift of the center of the positive (negative) AD anomaly to Greenland (in the Laptev Sea and East Siberian Seas) in the more recent period (2007–2021) from the vicinity of the Kara Sea and Laptev Sea (the Canadian archipelago) in the earlier period (1979–2006). Before the mid-2000s, a wave train was shown in the middle troposphere of Eurasia, and this teleconnection pattern of atmospheric circulation could have resulted in local warm and wet (cool and dry) anomalies over northern Russia and East Asia (Western Europe and the Far east). Since the mid-2000s, the wave train has experienced a notable adjustment that was conducive to East Asian and Arctic cooling, displaying anticyclonic anomalies around northern Eurasia and two cyclonic anomalies centered near the Arctic and East Asia. The presence of a cold Arctic anomaly was found to enhance westerly winds at high latitudes by modulating the meridional temperature gradient (MTG) and impeding the southward propagation of cold Arctic air. Additionally, the warmth of northern Eurasia may have also resulted in a reduction in the MTG between northern Eurasia and the mid-lower latitudes, favoring a weakening of zonal winds over the central region of Eurasia. The increased upper-level westerly winds over southern East Asia implied a weakened East Asian Summer Monsoon, which inhibited precipitation in northeast China.